SYNTHESIS AND EVALUATION OF ETHYL (4-(N-(THIAZOL-2-YL) SULFAMOYL) PHENYL)CARBAMATE (TSPC) AS A CORROSION INHIBITOR FOR MILD STEEL IN 0.1M HCL (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Laboratory synthesized ethyl (4-(N-(thiazol-2-yl)sulfamoyl)phenyl)carbamate (TSPC), characterized by 1H NMR spectroscopy, was evaluated as corrosion inhibitor of mild steel in 0.1M HCl using electrochemical techniques. Open circuit potential, potentiodynamic polarization and impedance spectroscopy were used to evaluate the inhibition efficiency of (TSPC) at various concentrations. The obtained electrochemical data indicated that (TSPC) acts as moderate corrosion inhibitor for mild steel in acidic media. It is found that the inhibition efficiency increases with the concentration of the inhibitor till 400ppm. The adsorption isotherm involving physisorption of (TSPC) at room temperature and the experimental data complied to the Langmuir adsorption isotherms and the negative values of the Gibb’s free energy of adsorption obtained suggested that inhibitor molecules have been spontaneously adsorbed onto the mild steel surface.